Introducing the RICE framework in paddy-duck farming: a novel approach to enhance the adaptive capacity of paddy farmers among asnaf community in managing the risk of climate change - Sayed, Khalid; Syakir, M. I.; Othman, Aimie Aisyah; Azhar, Badrul; Tohiran, Kamil A.; Nobilly, Frisco (Taylor and Francis Ltd., 2025)
The industrial revolution marked a transformative era in the history of rice cultivation, bringing significant changes to meet growing demand and addressing food security concerns. Maintaining paddy production through conventional practices has become increasingly challenging, particularly considering the projected impacts of climate change on both paddy productivity and farmers’ livelihoods. According to recent studies, rice-duck system application decreases nitrogen fertiliser by 57%, herbicides by 50%, expenditures by $296.3 M, increase income by $1523.9 ha−1, and cleaner production using organic waste recycling. The present study introduces the RICE (restore, integrate, circular, enhance) framework, proposed as an instrumental approach to explore strategic and sustainable solutions that go beyond a production-centric mindset. This framework considers the balance between present production demands and potential losses of ecosystem services in the long run. The RICE framework has the potential to serve as a strategic environmental, social, and governance (ESG) instrument for lembaga zakat negeri Kedah (LZNK). It promotes regenerative agriculture and seeks to improve the livelihoods of asnaf farmers within the smart sawah berskala besar asnaf (SSBA) scheme. By adopting this approach, LZNK can contribute to sustainable development by ensuring that present needs are met without compromising the ability of future generations to fulfill their needs.